The Minimum Competency Assessment Model Instrument Development Training for MTs Mathematics Teachers in Bandung - Jarnawi A. Dahlan; Dadang Juandi; Lukman; Nusrotul Bariyah; Amelia Defrianti Putri (Yayasan Payungi Smart Madani, 2025)
The Minimum Competency Assessment (AKM) is followed by students and is designed to measure reading and numeracy literacy as a cognitive learning outcome. In its development, AKM adopts the assessment system carried out by the OECD through PISA, so that it was first implemented and even now, in general, teachers still do not understand AKM which is based on numeracy literacy, and have not been able to develop measurement instruments according to standards. For the fulfillment of quality educational services for the community through improving the competence of teachers in AKM, community service is developed in the form of training. In order for the training to strengthen the understanding of numeracy literacy and the development of assessment instruments, this service is arranged in several stages. Seminar on strengthening numeracy literacy and its measurement, and the practice of developing AKM model instruments. Although the increase in participants' knowledge was not too high, the results of the evaluation of this service activity were responded to very well in service, responsiveness, and tangible evidence. The teacher's response to the implementation of service activities that have been carried out is generally considered very good. The seminars and workshops in the development of AKM model instruments have provided a lot of knowledge and experience in compiling standard instruments, so that not only for the needs of literacy measurement, but also for the needs of teachers in the development of learning outcome instruments. Therefore, it is important for the government (Ministry of Education and Ministry of Religion) or universities in the field of education to provide services for teachers in improving their numeracy understanding skills, and their skills in compiling AKM model instruments, so that they can be integrated into mathematics learning practices.